Examining a new model of destination choice behavior: An empirical study from Vietnam - Trong Tien Bao BUI (Tourism and Hospitality Management)
Purpose – The purpose of this study is to propose a new model, the M-TPB-D model, which combines the theory of planned behavior (TPB), the travel motivation theory, and the overall image of the destination. This model aims to provide a new perspective for understanding and predicting tourists’ visit intentions and leads to increasing destination choice behavior in the tourism destination context. Methodology/Design/Approach – To gain a comprehensive understanding of destination choice behaviour, a mixed methods approach combining quantitative and qualitative methods was used. Data was collected through a random sample survey of 630 domestic tourists travelling to Ho Chi Minh City. The final sample consisted of 459 usable questionnaires. Findings – The findings of the study confirm the causal relationship between the original TPB theory, pull-push motivation theory, overall image of the destination and destination choice behavior. This offers a novel insight into understanding destination choice behavior from the viewpoint of domestic tourists. Originality of the research – The study makes a significant contribution through the integration of multiple theories, resulting in a comprehensive understanding of the various factors that influence destination choice behavior. Furthermore, the study has implications for both theoretical implications and practical implications for destination marketing and management.